Specification of indoor climate design parameters at the assessment of moisture protective properties of enclosing structures - Kornienko Sergey Valer’evich (Vestnik MGSU, 2016)
Due to wide implementation of enveloping structures with increased heat-insulation properties in modern construction here appeared a necessity to assess their moisture conditions. Assessment of moisture conditions of enveloping structures is carried out according to maximum allowable moisture state basing on determining the surface of maximum damping. In relation to it the necessity of additional vapour barrier is checked using moisture balance equation. Though the change of indoor climate parameters in premises is not taken into account in moisture balance equations defined for different seasons. The author improves the method of calculating moisture protective parameters of enclosing structures according to the maximum allowable damping state for a year and a period of moisture accumulation. It is shown in this article that accounting of temperature and relative humidity change of inside air allows specifying calculated parameters of indoor climate in residential and office rooms in assessment of moisture protective properties of enclosing structures for the case of an effective enclosing structure with a façade heat-insulation composite system. Coordinates of the maximum moistened surface of the envelope depends on indoor climate design parameters. It is concluded that the increase of requirements for moisture protection of enclosing structures when using design values of temperature and relative humidity of internal air according to the Russian regulation (SP 50.13330.2012) is not always reasonable. Accounting of changes of indoor climate parameters allows more precise assessment of moisture protective properties of enclosing structures during their design.